Advanced Analysis of Clay Microporosity Using High-Resolution N2-Ar Adsorption Isotherms Coupled with the Derivative Isotherm Summation Method - Anwar El Azrak; Denys I. Grekov; Laurent Truche; Pascaline Pré (Molecules)
The textural properties of synthetic and natural clays in the sodium form and exchanged with tetramethylammonium cations (TMA+) were characterized using N2 and Ar physisorption isotherms at cryogenic temperatures. Specific surface areas and micro/mesoporous volumes were determined using the BET and the t-plot models. The t-plot analysis requires the use of reference isotherms measured at the same temperature on the surface of non-porous materials with an identical chemical composition. In order to better assess the effects of chemical heterogeneities in the clay particles, reference isotherms representative of silica surfaces were taken into account in the analysis of the t-curve and corrected to account for variations in curvature at the interface of the film adsorbed in the micropores. In addition, high-resolution Ar adsorption isotherms at 87 K were analyzed using the Derivative Isotherm Summation (DIS) method to quantify the energy contributions of adsorption sites and determine the fractions of basal and lateral surfaces of clay particles. The high-energy adsorption sites, identified in the low-pressure range, were attributed to intra-particle microporosity due to stacking defects and/or open inter-layer spaces. These sites were differentiated from those on the lateral and basal surfaces of the particles. A modification of the DIS method was proposed to measure these contributions and improve the fit with the experimental data. The results show that TMA+ cation exchange significantly increases the microporosity of clays compared to their sodic form, which can be attributed to the increased contribution of intra-particle adsorption sites due to interlayer expansion.